Design and fabrication of go-kart front suspension - Syahriza, Muhammad Irfan (2024)
Suspension is a system that are in an automotive vehicle. It is a crucial system because without it the car can’t properly function. It acts like a dampening for rough rides while maintaining its performance through handling by keeping all tires always in contact with the road. With that being said, this project requires a working front suspension for a go-kart. The most suitable type of suspension will be selected to integrate into the frame of the go-kart. By doing mock-ups and testing each type of suspension, a decision will be made. As a result, the thorough research will give a great performance to the go-kart.